Strategies and Challenges for Self-Management in Community Development Associations in Puntarenas - Lizano Rojas, Yeison (2026)
This research analyzes the factors that influence the success and operational effectiveness of community development associations in the First District of Puntarenas. A descriptive, mixed-method approach was applied through surveys and structured interviews with board members and key stakeholders. Findings indicate that 66.6 % of the associations have a strategic plan, although limitations remain in monitoring, evaluation, and community participation processes. Successful practices include income diversification, strategic alliances, and gender parity in governing boards. The study concludes that collaborative planning, effective communication, and shared responsibility between the State and the community are essential to promote inclusive and sustainable local development.